Knowledge sharing role in IT outsourcing - Ismail, Zuraini; Hussin, Husnayati; Suhaimi, Mohd. Adam; Abdul Karim, Nor Shahriza (2005)
Knowledge has emerged as a strategically significant resource to organization. In recent studies, there has been much interest in knowledge sharing between service receiver and service provider through an outsourcing partnership and its effect on information technology (IT) outsourcing success. Besides the frequent cited reasons of economic and technological benefits for IT outsourcing there is a growing concern of organizations evaluating its success or activity involved in IT outsourcing. Knowledge sharing is considered as one of the major motives of outsourcing partnership based on trust to ensure partnership quality. This study examines the relationship between knowledge sharing and IT outsourcing success. We argue that knowledge sharing is positively associated with IT outsourcing success. This paper further reports on the ongoing empirical work conducted on both public and private organizations in Malaysia that have outsourced their IT functions. We seek to investigate the issue of knowledge sharing from the service receivers’ perspective. It is anticipated that our research will elucidate the importance of knowledge sharing for both practitioners and knowledge management researchers, lens on IT outsourcing.